Postharvest Quality of Calcium Chloride-Treated Strawberry (Fragaria x ananassa cv. Festival) in CoolBot Storage - Lekhon, Sheikh Nymur Rashid; Khan, Shamim Ahmed Kamal Uddin; Kabir, Md Yamin (Journal of the Bangladesh Agricultural University, 2024)
Though strawberry is a popular and nutritious fruit gladly accepted worldwide, its delicate nature and high perishability makes it highly susceptible to postharvest loss. The objective of this study was to evaluate the postharvest quality attributes including shelf life of ‘Festival’ strawberry as affected by calcium chloride in CoolBot storage system. The experiment was conducted with four calcium chloride concentrations [control (no calcium), 1%, 2%, and 3% calcium chloride] following Completely Randomized Design with three replications. Each replication consisted of 400 g freshly harvested strawberry fruits which were dipped into the respective calcium chloride solutions for two minutes followed by 10-minutes air drying. The findings showed that 3% calcium chloride resulted in the highest anthocyanin content (40.62 mg 100g-1) and shelf life (10.33 days) along with the lowest fruit weight loss (11.18%). The 3% calcium chloride also maintained the higher fruit diameters (polar and equatorial) and firmness along with high level of titratable acidity, vitamin C, and total carbohydrate and low level of total soluble solids compared to the control. However, the lowest fruit spoilage (11.59%) was reported from 2% calcium chloride. Overall, 3% calcium chloride performed better regarding physical and chemical quality attributes and shelf life of strawberry at postharvest and therefore, it can be suggested for postharvest strawberry fruit preservation. However, further research could be conducted with other strawberry varieties to have a better understanding of postharvest strawberry preservations with calcium chloride in the CoolBot storage facilities. J Bangladesh Agril Univ 22(4): 547-557, 2024